Use of the CRISPR‐Cas9 System in Drosophila Cultured Cells to Introduce Fluorescent Tags into Endogenous Genes. Issue 1 (23rd December 2019) - Bosch, Justin A.; Knight, Shannon; Kanca, Oguz; Zirin, Jonathan; Yang‐Zhou, Donghui; Hu, Yanhui; Rodiger, Jonathan; Amador, Gabriel; Bellen, Hugo J.; Perrimon, Norbert; Mohr, Stephanie E.
Abstract: The CRISPR‐Cas9 system makes it possible to cause double‐strand breaks in specific regions, inducing repair. In the presence of a donor construct, repair can involve insertion or 'knock‐in' of an exogenous cassette. One common application of knock‐in technology is to generate cell lines expressing fluorescently tagged endogenous proteins. The standard approach relies on production of a donor plasmid with ∼500 to 1000 bp of homology on either side of an insertion cassette that contains the fluorescent protein open reading frame (ORF). We present two alternative methods for knock‐in of fluorescent protein ORFs into Cas9‐expressing Drosophila S2R+ cultured cells, the single‐stranded DNA (ssDNA) Drop‐In method and the CRISPaint universal donor method. Both methods eliminate the need to clone a large plasmid donor for each target. We discuss the advantages and limitations of the standard, ssDNA Drop‐In, and CRISPaint methods for fluorescent protein tagging in Drosophila cultured cells. © 2019 by John Wiley & Sons, Inc. Basic Protocol 1 : Knock‐in into Cas9‐positive S2R+ cells using the ssDNA Drop‐In approach Basic Protocol 2 : Knock‐in into Cas9‐positive S2R+ cells by homology‐independent insertion of universal donor plasmids that provide mNeonGreen (CRISPaint method) Support Protocol 1 : sgRNA design and cloning Support Protocol 2 : ssDNA donor synthesis Support Protocol 3 : Transfection using Effectene Support Protocol 4 : Electroporation of S2R+‐MT::Cas9 Drosophila cells Support Protocol 5 : Single‐cell isolation of fluorescent cells using FACS